Irrigation infrastructure quality management system toolkit for Sub-Saharan Africa using Ethiopia, Kenya and Uganda as a case study: volume II – parameter checklist - Amare, Melkamu; Abdella, Y.; Seid, Abdulkarim; Haileslassie, Amare (International Water Management Institute, 2024)
The issue of quality in developing small-scale irrigation projects (SSIPs) in Sub-Saharan countries has become a concern. This necessitated the development of a quality management system (QMS) toolkit covering all phases of irrigation project development. The current toolkit was developed to provide guidance and support to establish a robust system that aligns with irrigated agriculture development best practices, standards and regulatory requirements. Literature from the three focal countries – Ethiopia, Kenya and Uganda – was reviewed and stakeholder consultations, field visits and focus group discussions were conducted to learn lessons and gain insight to enrich the proposed parameters and checklists. Based on the lessons learned, the QMS toolkit was created, including a comprehensive set of guidelines, checklists, tools, resources, forms and templates that can help irrigation agencies and stakeholders at all levels implement and maintain an effective quality management system. It is an essential tool for organizations such as irrigation and agriculture ministries, regional bureaus and county offices to assess and improve their performance by meeting quality requirements, standards, regulations and specifications. The toolkit is prepared in two volumes. Volume II is a series of checklists of key parameters that need to be considered when implementing an irrigation quality management system. The checklists cover the first three phases and associated stages, components and subcomponents of an irrigation development process. These checklists will aid in streamlining quality management review processes and ensure consistency in quality control practices. By following the checklists in this volume, irrigation implementing agencies (IAs), organizations and project managers can ensure that each task is completed correctly and in compliance with established procedures, guidelines, methodologies, standards and technical specifications. Volume II also provides QMS workflow charts for each phase and stage of an irrigation project, which serve as quality control mechanisms that track whether tasks and services provided are fully completed and adhere to specified standards. This volume also contains proposed institutional arrangements for implementing a QMS initiative. These arrangements include a generic organogram, human resource requirements and job descriptions for key positions within the proposed QMS implementation team.